Transforming cultures: Open Access and the research-teaching nexus - BRENNAN, NIAMH (My University, 2011)
A cultural transformation is needed to overcome the paradox at the heart of academia, namely: the people involved in teaching and research communities are often the same people `just wearing different hats? and convergence is already taking place in the world around them - so how is it possible that their activities can remain separate? Ireland?s HEA-supported open access research and teaching initiatives were used to illustrate the opportunities which are available in countries throughout Europe and to point the way forward. The authors reiterate the recommendation to the European Commission made in the Ghent Declaration of February 2011 ? 'to develop policies, research programmes and infrastructure platforms that support and advance the convergence of the four open initiatives' - open access, open data, open source software and open educational resources, noting that 'additional work is needed in other areas to achieve a broadening of research, scholarship and learning.'
eInfraNet Open Workshop
PUBLISHED
Noordwijk aan Zee, Netherlands
Keywords: Open Access research; Open Educationa Resources (OER); Research-Teaching nexus; Research-led teaching; Inclusive Society; Intelligent Content & Communications; International Development